Peer Teaching Method to Support the Students’ Learning Motivation In Arabic Speaking Skills During The Covid-19 Pandemic - Nurul Wahdah; Mahfuz Rizqi Mubarak; Hamidah Hamidah; Noor Amalina Audina; Aulia Mustika Ilmiani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The current covid-19 pandemic phenomenon has a major impact on the learning process at various universities in Indonesia. The adoption of the online lecture system caused by the pandemic has become a problem for some lecturers who are still unfamiliar with technological development. This situation is also experienced by a lecturer who teaches the Speaking Skill Course at a Higher Education in Central Kalimantan Province as a consequence of lacking motivation for the students to attend Speaking Course. To overcome this demotivation, the Arabic Students’ Association at the tertiary education institution organizes Speaking learning using the ”Peer Teaching Method. Therefore, this study aims to explore the speaking skill learning process. This study uses a qualitative approach with a case study type and uses two data collection techniques, namely observation and interviews. This study produced two findings. First, there were several steps used by the organizational coordinator in implementing Speaking Skill learning using the peer teaching method, namely (1) selecting prospective tutors based on their scientific capacity and experience in the field of Arabic language learning, (2) Active learning process speaking skill organized by tutors using various interactive games such as nurakkizu, word chain, and ice breaking. Second, there are several motivational factors for students in participating in speaking skill learning using the peer teaching method, namely (1) The convenience of interaction between tutors and students is caused by the age distance that is not too far, (2) Peer tutor creativity in organizing innovative Speaking Skill learning, and (3) flexibility in communication time between tutors and students.